Information Communications Technology Architecture and Implementation Scheme of Smart Energy System - Tengbo DING; Hongbo LIU; Pin WU (发电技术)
Based on social and economic development, environmental protection needs, industrial policy guidance and other factors, smart energy will bring a new round of tremendous changes to the traditional energy structure. The rapid development of modern information communications technology (ICT) provides strong technical support for the transformation and upgrading of traditional energy to smart energy. The whole smart energy system will be guided by innovative scenario demand, supported by the deep support of cross-border scientific and technological forces, and drive the structural upgrading of the whole energy and related industrial chain. An ICT framework of energy system suitable for smart energy application scenario was proposed, which combined cloud computing, big data, internet of things (IoT), mobile communication, artificial intelligence, blockchain and other emerging technologies to enable traditional energy system. It runs through the bottom to the top of energy system, and realizes the comprehensive integration of energy flow, information flow and value flow of intelligent energy system.